Conductivity and morphological studies of poly(vinyl alcohol)-magnesium triflate-ethylene carbonate gel polymer electrolyte / Nurul Izzati Ali ...[et al.] - Ali, Nurul Izzati; Zaharuddin, Siti Norzahirah; Mohammad Azis, Nur Aida Syarmeen; Mohd Rafi, Noraishah Syuhada; Zainal Abidin, Siti Zafirah (Universiti Teknologi MARA, 2021)
Gel polymer electrolyte based on poly (vinyl alcohol)(PVA)-magnesium triflate (MgTf) incorporating with different weight percentage (wt.%) of ethylene carbonate (EC) as plasticizer has been prepared by using solution casting method. The ionic conductivity of PVA-MgTf-EC gel polymer electrolyte has been determined by using Electrochemical Impedance Spectroscopy (EIS) and has achieved an optimum value at 1.26 x 10-4 S.cm-1 when 50 wt.% of EC is added into the system. Fourier Transform Infrared Spectroscopy (FTIR) has been performed to study the molecular interaction between components in PVA-MgTf-EC gel polymer electrolyte. The complexations between the materials used in the electrolyte system are observed based on the shifting of bands and changes in the intensity of peaks in FTIR spectra. The morphological behaviour of electrolytes has been studied by using Field Emission Scanning Electron Spectroscopy (FESEM) to observe the changes of PVA-based gel polymer electrolytes when EC is added to the system. The amorphous peak of PVA-based electrolyte is observed to become broaden with the addition of plasticizer, results in increment in the amorphousness nature of the electrolyte which is determined by X-ray Diffractometer (XRD).